Magnetic coils for quantum biology - Zhang, Wei (2014)
Experiments on magnetoreception of cockroaches require a large uniform magnetic field. To design a magnetic coil producing such uniform magnetic fields, we calculate and simulate the fields produced by square Helmholtz coil and the Meritt four square coil system. We find the four square coil system produces a more uniform magnetic field than the square Helmholtz coil and over much larger area. We build three four-square-coil systems so that the arbitrary magnetic field can be prepared in 3D.